SURVIVAL AND INITIAL GROWTH OF SEEDLINGS PRODUCED IN DIFFERENT CONTAINERS AND THE USE OF MULCHING IN ANTHROPIZED AREA - Thairini Claudino Zavistanovicz; Maristela Machado Araujo; Suelen Carpenedo Aimi; Álvaro Luís Pasquetti Berghetti; Claudia Costella; Matheus Roberto da Silva (Revista Árvore)
ABSTRACT The demand for seedlings of native tree species for the restoration of altered areas has increased considerably. Therefore, knowing the strategies that favor quality seedling production in the nursery, in addition to survival, growth, and development in the field, is important. This study was to evaluate the survival and initial growth of Inga vera Will and Schinus terebinthifolius Raddi, after 24 months of planting, seedlings in an anthropized area. The experiment was conducted using a factorial scheme (2×2), considering the types of containers used in the production of seedlings and the presence or absence of mulching in the surroundings. The survival of the seedlings, as well as their morphophysiological attributes, was verified 24 months after planting. I. vera presented a higher average survival for seedlings grown in plastic bags (86.7%), whereas S. terebinthifolius did not show any difference between treatments. The morphological attributes of increased height (IncH), diameter of the stem (IncSD), crown area (AC), and shoot dry mass (SDM) were favored by the use of plastic bags in seedlings of I. vera. For S. terebinthifolius, the plastic bag favored only IncH, equaling the seedlings produced in containers for the other variables. Using mulching was ineffective in helping the growth of either species, and the physiological attributes were similar for all the treatments tested. Aiming at the high survival and rapid growth of seedlings in the field, it is recommended to produce I. vera in 1.5 L plastic bags, while S. terebinthifolius seedlings can be produced in 180 cm3 containers. Therefore, using mulching as a culture treatment for both species should be investigated in future studies.